2021
DOI: 10.1186/s12967-021-02954-8
|View full text |Cite
|
Sign up to set email alerts
|

SRPK1/AKT axis promotes oxaliplatin-induced anti-apoptosis via NF-κB activation in colon cancer

Abstract: Background Colorectal cancer is the third most common diagnosis. Oxaliplatin is used as first-line treatment of colon cancer. However, oxaliplatin resistance greatly reduces its therapeutic effect. SRPK1 involves in pre-mRNA splicing and tumorigenesis. How SRPK1 mediates drug resistance in colon cancer is unknown. Methods The expression of SRPK1 was analyzed in the TCGA and the CPTAC pan-cancer samples and detected in colon cancer cell lines and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
1
15
0
2
Order By: Relevance
“…The current author proposes that primary afferent peripheral terminal hyperexcitation with “leakiness” at Piezo2 is such a pathological condition in DOMS. Accordingly, it is not surprising that platinum-analogue drugs also elevate ROS production as the primary mechanism of platinum-induced peripheral neuropathy [ 110 ] with the activation of the NF-kappa B pathway [ 111 ].…”
Section: Oxidative Stress and Redox Imbalancementioning
confidence: 99%
“…The current author proposes that primary afferent peripheral terminal hyperexcitation with “leakiness” at Piezo2 is such a pathological condition in DOMS. Accordingly, it is not surprising that platinum-analogue drugs also elevate ROS production as the primary mechanism of platinum-induced peripheral neuropathy [ 110 ] with the activation of the NF-kappa B pathway [ 111 ].…”
Section: Oxidative Stress and Redox Imbalancementioning
confidence: 99%
“…SRPK1 silencing was found to promote cleaved poly (ADP-ribose) polymerase (PARP) and b-cell lymphoma extra S (BCL-xS) expression in cancer cells. NF-κB signalling was also found to be downregulated in response to SRPK1 silencing and this was associated with a significant reduction in oxaliplatin IC50 values on MTT assay [30]. Plascencia et al, also previously provided evidence linking SRPK1 expression to oxaliplatin resistance in colorectal cancer [59].…”
Section: Colorectal Cancermentioning
confidence: 84%
“…Thirteen studies explored the role of SRPK1 in colorectal cancer [3,25,[27][28][29][30][55][56][57][58][59][60][61]. SRPK1 expression was generally found to be elevated in colorectal cancer, with the exception of the mucinous subtype [3, 25, 27-30, 60, 61] (Table 1).…”
Section: Colorectal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The target genes of FOXP4-AS1 were further predicted and functionally annotated. SNORA56, SRPK1, and PRICKLE4 were significantly co-expressed with FOXP4-AS1 and played significant roles in breast cancer (34), NPC (35), HCC (36), lung adenocarcinoma (37), colon cancer (38) and ovarian cancer (39). Additionally, it has been shown that FOXP4-AS1 was interrelated with various functions, including double-strand AS1 may be associated with DNA replication, transcription, and cell cycle phase of tumor cells.…”
Section: Discussionmentioning
confidence: 99%